The Political Geometry of Statistical Tables. - Zakim, Michael (Journal of the Early Republic)
Democracy was a dangerously disordered form of politics, coming to power by overturning the organic foundations of America's traditional agrarian order. New sources of authority were consequently required for stabilizing this new style of self-government. Statistics were one such source, serving as a post-absolutist method for establishing objective truth, if not certainty. The fluid relations fixed by the statistics were displayed in the rows and columns of the "cross-table," whose strict geometries seemed to be anchored in self-organizing scientific laws independent of our making. In fact, the statistical table was a highly engineered event. Moving such immense quantities of information, and the enormous administrative effort required to generate that information, onto the printed page was an unequivocal sign of its man-made character, mobilizing a vast bureaucracy, taxonomic schemes, and a rich repertoire of visual effects. This artificial provenance of the table underscores the discursive character of modern objective truth while constituting a critical chapter in the production of modern liberalism.